Genetic variations in MicroRNA genes and cancer risk: A field synopsis and meta‐analysis. (6th March 2020) - Park, Jae Hyon; Jeong, Gwang Hun; Lee, Kwang Seob; Lee, Keum Hwa; Suh, Jin‐Soon; Eisenhut, Michael; van der Vliet, Hans J.; Kronbichler, Andreas; Stubbs, Brendon; Solmi, Marco; Dragioti, Elena; Koyanagi, Ai; et al.
Abstract: Background: Cancer risk has been associated with certain gene variations in microRNA (miRNA), but conflicting evidence warrants re‐assessing of significant results in meta‐analyses. We summarized published meta‐analyses that assess the associations between miRNA polymorphism and cancers to show the validity of the findings. Method: We searched PubMed and investigated the results of meta‐analyses published through November 2018. We re‐assessed the results based on false‐positive report probability (FPRP) to test the noteworthiness of the associations. Results: Sixty‐eight miRNA polymorphisms in 45 meta‐analyses associated with cancer were included. Four (7.4%) and sixteen (25.0%) single nucleotide polymorphisms (SNPs) were noteworthy (FPRP < 0.2) at a prior probability of 0.001 for interesting candidate genes and a statistical power to detect an odds ratio (OR) of 1.1 and 1.5, respectively. The four miRNA SNPs noteworthy at an OR of 1.1 were as follows: miR‐146a/rs2910164 Cvs.G; miR‐27a/rs895819 Cvs.T; miR‐423/rs6505162 Cvs.A; and miR‐605/rs2043556 Cvs.T. The 16 SNPs noteworthy at an OR of 1.5 include the four genotype comparisons at an OR of 1.1, and the additional 12 genotype comparisons were as follows: miR‐196a2/rs11614913 Tvs.C; miR‐27a/rs895819 GGvs.AA + AG; miR‐196a2/rs11614913 C vs.T; miR‐146a/rs2910164 Gvs.C; miR‐196a2/rs11614913 Tvs.C; miR‐146a/rs2910164 Cvs.G; miR‐499/rs3746444 homozygous model; miR‐146a/rs2910164 CCvs.GG + GC; miR‐499/rs3746444 TCvs.TT; miR‐499/rs3746444 GAvs.AA; miR‐146a/rs2910164 CCvs.GG; and miR‐499/rs3746444 Gvs.A. No association was noteworthy at a prior probability of 0.000001. Conclusion: Out of 68 published associations of miRNA polymorphisms with cancer, sixteen have shown noteworthiness in our re‐assessing meta‐analysis. Our findings summarize the results of meta‐analyses on the association of cancer with SNPs and underline the importance of interpreting results with caution.